Evidence for the Influence of Confucian Filial Piety on Deviancy Among Young People - Nicholas Lassi (Syntax Corporation Indonesia, 2023)
This study is a test of Confucian filial piety’s ability to influence deviant behavioral outcomes among young people. Variables examining the acceptance/rejection of parental guidelines by young people, representing levels of filial piety, were collected from the NLSY97. These acceptance/rejection of parental guidelines variables were tested by delinquency and substance use outcome variables. The data was attained from the first three waves of responses from the NLSY97, with a sample of 8,985 people from the United States within the ages of 12-19. Confucian theory was supported by this examination, even after controlling for several variables including ethnicity, gender, year of birth, household income, parent education, etc. Generally, the more that parental guidelines were rejected, the greater the probability for delinquency and substance use. Limit-breaking in the years 1997 (both youth and parent reports) and 1999 (youth report) produced significantly greater levels of delinquency and substance use. Limit-breaking in 1998 (youth report) had no effect on delinquency and substance use. When young people reject the limits set by their parents, when they reject filial piety, there is a greater likelihood that limits will be broken within society as well. This study adds support to Confucian criminological theory.